Surface Stabilizes Ceria in Unexpected Stoichiometry - Olbrich, Reinhard (2017)
The prototype reducible oxide ceria is known for its rich phase diagram and its ability to absorb and deliver oxygen. The high oxygen storage capacity is the basis for the use of ceria in catalytic and sensor applications where the surface plays a paramount role for device functionality. By direct imaging, we reveal the reconstruction of the ceria (111) surface in five periodic structures representing reduction stages ranging from CeO2 to Ce2O3. Theoretical modeling shows that the (√7 × 3)R19.1° reconstruction, representing the previously unknown Ce3O5 stoichiometry, is stabilized at the surface but cannot be assigned to a bulk structure. Statistical modeling explains the thermodynamic stability of surface phases depending on the oxygen chemical potential and the coexistence of certain phases over a range of temperatures. These results are crucial for understanding geometric and electronic structure-function correlations in nanostructured ceria and the rational design of novel ceria-based functional systems.